2019
DOI: 10.1177/0300060519893870
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of MIF polymorphism and serum levels of MIF with glucocorticoid sensitivity of sudden sensorineural hearing loss

Abstract: Objective This study explored the relationship between macrophage migration inhibitory factor (MIF) gene polymorphism (−173G/C) and glucocorticoid sensitivity in sudden sensorineural hearing loss (SSNHL). Methods A total of 120 patients with SSNHL were divided into a glucocorticoid-sensitive group and a glucocorticoid-resistant group. A group of 93 healthy individuals served as the control group. Serum MIF levels of the participants were measured and MIF genotyping was performed. Results The frequency of the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…MIF confers resistance to steroids by suppression of the nuclear factor kB (NF-kB) inhibitor (IkB) and mitogen-activated protein kinase (MAPK) inactivator MAPK phosphatase-1; furthermore, it reverts the cytokine-induced suppression of cytoplasmatic phospholipase A2 provoked by GCS and activates the release of arachidonic acid, which results in an increase in inflammation due to the transcription of pro-inflammatory cytokines such as TNF and IL-6 [ 19 , 24 ]. Zhu et al observed, in non-rheumatic disease, that non-responders to GCS had higher levels of MIF [ 25 ]. Furthermore, the evaluation of MIF serum levels and their association with GCS resistance in SLE has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…MIF confers resistance to steroids by suppression of the nuclear factor kB (NF-kB) inhibitor (IkB) and mitogen-activated protein kinase (MAPK) inactivator MAPK phosphatase-1; furthermore, it reverts the cytokine-induced suppression of cytoplasmatic phospholipase A2 provoked by GCS and activates the release of arachidonic acid, which results in an increase in inflammation due to the transcription of pro-inflammatory cytokines such as TNF and IL-6 [ 19 , 24 ]. Zhu et al observed, in non-rheumatic disease, that non-responders to GCS had higher levels of MIF [ 25 ]. Furthermore, the evaluation of MIF serum levels and their association with GCS resistance in SLE has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…MIF can antagonize glucocorticoid-mediated immunosuppression via affecting NF-κB/IκB signaling or triggering the mitogenactivated protein kinase (MAPK) signaling (5,25,26). Accordingly, MIF promoter polymorphisms were associated with clinically defined steroid resistance in autoimmune and inflammatory diseases such as juvenile idiopathic arthritis, inflammatory bowel disease and sudden sensorineural hearing loss (27)(28)(29). However, the association between MIF -173 G>C polymorphism and steroid resistance in INS is the most studied, but the results are not consistent.…”
Section: Discussionmentioning
confidence: 99%
“…Mif knockout mice appear to be more susceptible to agerelated hearing loss than wildtype mice (39). Some evidence furthermore suggests that SSNHL patients demonstrate higher levels of circulating MIF when compared to normal-hearing patients, and that higher circulating MIF levels and possibly MIF-related SNPs may impact steroid-responsiveness of SSNHL (38,41). Together, these observations suggest that genes implicated in hearing los susceptibility are involved at the tissue and cellular level in the cochlea in SSNHL.…”
Section: Localization Of Ssnhl-implicated Genes To Innermentioning
confidence: 95%